The Impact of Current Ratio, Debt to Equity Ratio and Total Asset Turnover on Return on Equity in Construction Companies Listed on The Indonesia Stock Exchange from 2012 to 2017 - Widiantoro, Fian Martino; Prasetyanta, Agus; Kaloeti, Ade Kristianus (Universitas Kristen Immanuel, 2022)
This research aims to determine the effect of the current ratio, debt to equity ratio, and total asset turnover on return on equity either partially or simultaneously on construction companies listed on the Indonesia Stock Exchange in 2012-2017. The population of 15 companies and the sample taken as many as 6 companies, sampling using the purposive sampling method. Data analysis techniques used descriptive statistical tests, classic assumption tests, regression analysis, and determinant coefficients. The test results show that partially the current ratio has no effect, while the debt to equity ratio and total asset turnover have a significant effect on return on equity. Simultaneously the three independent variables have a significant effect on return on equity. The research shows the coefficient of determination is able to explain the effect of the system on return on equity of 58.1% and the remaining 42.9% is influenced by variables not included in this research.